Mineral natural table waters as a component of sanatorium-resort children rehabilitation complexes in the remission of oncological diseases - Shapovalova, A. A.; Babov, K. D.; Badiuk, N. S. (Journal of Education, Health and Sport, 2017)
Urgency. High rates of oncological diseases (11.5-12.0 per 10.000 of children's population) dictate the need for comprehensive approaches to the organization of the rehabilitation process. The objective: to justify the advisability of using mineral natural table water in the period of oncopathology remission in children under conditions of sanatorium-and-spa rehabilitation. Materials and methods. The algorithm of the children’s examination included the study of anamnesis, complaints, initial nonspecific adaptive-adaptation reactions (according to the general clinical analysis of blood). The general rehabilitation complex (GRC) included a dose-sparing motion regimen; climatotherapy, diet food, therapeutic exercises in special medical groups, singlet-oxygen cocktail, phytotea (holosas with ascorbic acid), psychological support. In addition to GRC in 2 therapeutic complexes (TC) mineral natural table waters (MW) Truskavetskaya Akva-Eko mineral water (TC1 after treatment of solid tumors) and Morshinskaya (TC2 after treatment of oncohematological diseases). Results. The general tendency to the mend of sick children state under the influence of TC1 was established in comparison with GRC. It manifested in significant changes of various levels (P <0.05, P <0.01) of all symptom-complexes without exception. At the end of the rehabilitation course with the usу TC2, 50% of children reported a decrease of rapid fatigue, 30% decreased irritability, 27.7% improved appetite, and 22.2% decreased flatulence. Pain syndrome in the right upper quadrant disappeared in 16.7% of the children, and in 33.3% of the patients epigastric pain disappeared. LK1 caused a significant increase of children with adaptive training reactions and quiet activation, decrease in the reactions of increased activation; the disappearance of stress and excessive activation reactions. The use of TC2 facilitated a threefold decrease in the frequency of manifestations of the IV degree of stress of nonspecific adaptation reactions of low level, the disappearance of initial stress reactions in 33.3% of children, doubling the frequency of training reactions while maintaining the frequency of quiet activation reactions and the tendency to increase the reactions of increased activation. Conclusion. Additional in cycles assignment to the GRC MW Truskavetskaya Akva-Eko and Morshinskaya for the children after solid tumors and oncohematological diseases treatment allows to reliably reduce the manifestations of asthenic, pain and dyspeptic syndromes and to ensure the optimization of nonspecific adaptive reactions of the body.